Systemic Risk and Complex Networks in Modern Financial Systems - Pacelli, Vincenzo; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book is a groundbreaking exploration of systemic risk in modern financial systems. Through its theoretical and empirical investigations, it reveals the multidimensionality of systemic risk, the transmission channels of crises, and the interlinkages between physical, transition, and financial risks. It introduces cutting-edge methodologies, including prediction and optimization models based on complex networks, multilayer networks and eXplainable Artificial Intelligence (XAI) approaches, to forecast and measure systemic risk and financial crisis. It provides insight for academics, practitioners, policy and supervisory authorities, and bankers and financial market operators on understanding the links that determine the propagation of financial crises and the emergence of systemic risks. This book is essential for those wishing to better understand systemic risk and its implications.
Systemic Risk and Complex Networks in Modern Financial Systems -- Systemic Risk and Network Science: A Bibliometric and Systematic Review -- A Holistic Journey into Systemic Risk: Theoretical Background, Transmission Channels and Policy Implication -- Macro-prudential Policies to Mitigate Systemic Risk: An International Overview -- Systemic Risks and Multilayer Financial Networks: From Contagion to Mitigation.
Keywords: Financial risk management; System theory; Financial engineering; Risk Management; Complex Systems; Financial Technology and Innovation